Efeitos do trinexapac-ethyl e do nitrogênio na produtividade da cultura do trigo - Penckowski, Luis Henrique (2006)
The use of nitrogen in the culture of the wheat seeks the increase of the productivity.However, it also increases the probability of occurrence of the lodgnign. That can be avoided with the application of growth regulators. In that sense, he took place a field experiment, in the city of Castro, PR, seeking to evaluate the effects of the application of the trinexapac-ethyil in different times and of doses of nitrogen on wheat, cultivars (VANTE and BRS 77). The experimental field was blocks at random in factorial outline 4x4 with four repetitions. The treatments consisted of the combination of 100 g i.a ha -1 of applied trinexapac-ethyl among the 1º and 2º visible knot of the wheat, 2º and 3º visible knot, sequential application on half of the dose between the 1º and the 2º visible knot and half between the 2º and 3º visibleknot, besides the witness without trinexapac-ethyl apllication. The doses of nitrogen were of 90, 135, 180 and 225 kg.ha - 1 fot to AVANTE and 60,90, 120 and 150 kg.ha - 1 for to BRS 177. They were certain the stand, tillers numbers for plant, height of plants, diameter of the stem, lengthof the stem, length of thes stem among the leaf flag unitl the insert of the erar, lodging in the antesis and in the pre-cropo haverst, tenor of nitrogen in the leaves, yield and yield componentes and industrial quality of thewheat. The trinexapac-ethyl was efficient in reducing the length of the he/she enters us, reducidng the height of the plants and lodging percentage, being the moment of application of hte trinexapac-ethyl that promotes larger effects in the height of plants in between the 2º and 3º visible knot. The application of hte trinexapac - ethyl mainly in the phase of 1º and 2º visivle knot or 2º and 3º visible knot promoted significant increase of the ears number and in the productivity of grains when compared to the treatment without application of the growth regulator in cultivar AVANTE, what didn t happen for to cultivar BRS 177. The increase of the dose of nitrogen increases the tenor of the element in the plant and it promotes larger lodging factor that can be mininmized by the application of the growth reducer. It didn t happen earnings about the production components and productivity for the increase of the doses of nitrogen, showing that the recommended doses assistg the demands of the cultivars. The industrial quality of hte wheat was not influenced by the trinexapac-ethyl application, except for to cultivate BRS 177 that presented increase of theweight hectolitric in the treatments with trinexapac-ethyl. The increase of the dose of nitrogen increased the amount of gluten humid, dry and of the Force of Gluten (W) and it reduced the weight hectolitric and Falling Number to cultivar BRS 177, in cultivar AVANTE the doses of N didn t influence the parameters regarding the industrial quality